Evidence on Green Tea–Derived Compounds for Dental Erosion Prevention: An Umbrella Review of Review-Level Studies - Uzma Parveen Qureshi; Ladusingh Rajpurohit; Vini Mehta; Reshma Rameshrao Ghaytidak (Natural Resources for Human Health, 2026)
Background: Erosion of the teeth, also referred to as erosive tooth wear, represents the irreversible loss of the hard tissues of the teeth due to impact of acids. Besides the role of fluorides, other compounds, like polyphenols, have been studied for the prevention. Compounds like epigallocatechin gallate, found in the leaves of the Camellia sinensis (green tea) plant, have potential to prevent degradation of the matrix and the pellicle, thus preventing dental erosion. Objective: This umbrella review aims to critically appraise the review level evidence on the effects of the use of green tea and its active compounds on dental erosion. Methods: An umbrella review was conducted following the PRISMA 2020 protocol. Electronic search of various databases, such as PubMed/MEDLINE, Scopus, Web of Science, Embase, and the Cochrane Library, was conducted to find systematic reviews and meta-analyses on green tea and dental erosion. Results: Six systematic reviews were included. The evidence supports the notion that green tea-derived compounds have a protecting outcome on dentin erosion, especially in laboratory and in situ study’s. Evidence on enamel was more variable. The only quantitative systematic review found that green tea-derived compounds resulted in significant reductions in dentin surface loss, but with high heterogeneity. The quality of evidence ranged from high to critically low, with overall low certainty for dentin, very low for enamel and clinical outcomes. Conclusion: The green tea polyphenols have shown promise as adjuncts to erosion prevention. However evidence is mainly experimental and clinical trials are required to support the effectiveness.